A dry cold sintering to Ta doped-lithium lanthanum zirconate solid electrolyte for all-solid-state lithium metal battery - Rahmawati, Fitria; Alaih, Imam Shofid; Rosalin, Azka W; Nurcahyo, I F; Nursukatmo, Hartoto; Nilasary, Hanida; Oktaviano, Haryo S.; Raihan, Edo; Muzayanha, Soraya U.; Handaka, Muhammad F. A. (Center of Biomass & Renewable Energy (CBIORE), 2024)
Solid electrolyte is the essential part in all-solid-state battery (ASSB), in which the sintering step is vital to get a dense and high ionic conductivity. However, Li-loss frequently occurs at a high temperature, causing ionic conductivity to drop. This research investigated a dry-cold sintering process (dry-CSP) to Ta doped-LLZO (LLZTO), in which the LLZTO powder was pressed by cold isostatic pressing (CIP) at 40 MPa without solvent addition and then heated at 300oC for 2h. XRD analysis found that LLZTO300C40P remains crystallized in a single cubic with ionic conductivity of (3.02 0.53) x 10-5 Scm-1, which is higher than another result in Al doped-LLZO by CSP uniaxial pressing and with moistened-solvent (wet-CSP). The feasibility was tested by preparing a coin cell with a LiCoO2 cathode and Li metal anode. Cyclic voltammogram of the LCO-LLZTO300C40P-Li ASSB provides a high current density representing a higher electrochemical reaction rate inside the full cell. The battery ran well with an initial charging capacity of 88 mAh/g, and a discharge capacity of 50 mAh/g, providing 56.8 % Coulombic Efficiency. An interface engineering between electrode-solid electrolyte is essential to develop the ASSB performance.